Reviews of recent publications (Studies in 20th & 21st Century Literature, 1995)
Adelson, Leslie A. Making Bodies Making History: Feminism and German Identity by Sander L. Gilman Barrat, Barnaby B. Psychoanalysis and the Post-Modern Impulse: Knowing and Being Since Freud's Psychology by Mitchell Greenberg Calinescu, Matei. Rereading by Laurence M. Porter Donahue, Neil H. Forms of Disruption: Abstraction in Modern German Prose by Burton Pike Feminisms of the Belle Epoque, A Historical and Literary Anthology. Jennifer Waelti-Walters and Steven C. Hause, Eds. (Translated by Jette Kjaer, Lydia Willis, and Jennifer Waelti-Walters by Christiane J.P. Makward Hutchinson, Peter. Stefan Heym: The Perpetual Dissident by Susan M. Johnson Julien, Eileen. African Novels and the Question of Orality by Lifongo Vetinde Kristof, Agota. Le Troisième Mensonge by Jane Riles Laronde, Michel. Autour de roman beur: immigration et identité by Mireille Rosello Livingstone, Angela. Art in the Light of Conscience. Eight Essays on Poetry by Marina Tsvetaeva by Catherine Ciepiela Sarlo, Beatriz. Jorge Luis Borges: A Writer on the Edge by Maria Elena Solifio Sitney, P. Adams. Modernist Montage by Georgiana M.M. Colvile Vishevsky, Anatoly. Soviet Literary Culture of the 1970s: The Politics of Irony by Eric Lozowy Wang, David Der-wei. Fictional Realism in Twentieth-Century China: Mao Dun, Lao She, Shen Congwen by Xiaobing Tang
Keywords: Leslie A. Adelson; Making Bodies Making History: Feminism and German Identity; Sander L. Gilman; Barnaby B. Barrat; Psychoanalysis and the Post-Modern Impulse: Knowing and Being Since Freud' s Psychology; Mitchell Greenberg; Matei Calinescu; Rereading; Laurence M. Porter; Neil H. Donahue; Forms of Disruption: Abstraction in Modern German Prose; Burton Pike; Feminisms of the Belle Epoque A Historical and Literary Anthology; Jennifer Waelti-Walters; Steven C. Hause; Jette Kjaer; Lydia Willis; Christiane J.P. Makward; Peter Hutchinson; Stefan Heym: The Perpetual Dissident; Susan M. Johnson; Eileen Julien; African Novels and the Question of Orality; Lifongo Vetinde; Agota Kristof; Le Troisième Mensonge; Jane Riles; Michel Laronde; Autour de roman beur: immigration et identité; Mireille Rosello; Angela Livingstone; Art in the Light of Conscience. Eight Essays on Poetry by Marina Tsvetaeva; Catherine Ciepiela; Beatriz Sarlo; Jorge Luis Borges: A Writer on the Edge; Maria Elena Solifio; P. Adams Sitney; Modernist Montage by Georgiana M. Colvile; Anatoly Vishevsky; Soviet Literary Culture of the 1970s: The Politics of Irony; Eric Lozowy; David Der-wei Wang; Fictional Realism in Twentieth-Century China: Mao Dun Lao She Shen Congwen; Xiaobing Tang